TEACHING ENGLISH THROUGH YOUTUBE: GRAMMAR VIDEO ANALYSIS OF THREE BRAZILIAN YOUTUBE CHANNELS DEDICATED TO EFL TEACHING - Aline de Azevedo Fay; Juliana Matias (University of Kuningan, 2019)
The objective of this research is to analyze grammar lessons of three Brazilian YouTube Channels of English as a Foreign Language. It compares the approaches applied by each teacher in their videos and investigates if the lessons approach the explanation of meaning, use, and form of the grammar. It also aims to find out if the lessons are hackneyed regarding the online learning environment. The analysis consisted of watching two videos of the YouTube channels English in Brazil, Inglês Compartilhado and Mairo Vergara. The results showed that out of the six videos, five contained a grammar explanation that addressed meaning, use, and form of the language. They also adopted the deductive approach to grammar teaching. Only one video did not explain the grammar (quantifiers), but a trick to memorize the use of quantifiers. As for technology, the main tool teachers used was captions to illustrate example sentences of the grammar. Other tools consisted of the use of the software ‘Notepad’ and animation. Thus, there was not an innovation on the videos regarding technology. Future research is needed to understand if there is the necessity to apply cutting-edge tools to teach on YouTube and if it is mandatory to review and to adapt the pedagogical practices for language learning YouTube videos.